Cystic Fibrosis-Related Diabetes - Kayani, Kayani; Mohammed, Raihan; Mohiaddin, Hasan (Frontiers in Endocrinology, 2018)
Cystic fibrosis (CF) is the most common autosomal recessive disorder in Caucasian populations. Individuals with CF have seen significant increases in life expectancy in the last 60 years. As a result, previously rare complications are now coming to light. The most common of these is cystic fibrosis related diabetes (CFRD), which affects 40-50% of CF adults. CFRD significantly impacts the pulmonary function and longevity of CF patients, yet a lack of consensus on the best methods to diagnose and treat CFRD remains. We begin by reviewing our understanding of the pathogenesis of CFRD, as emerging evidence shows the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) also has important roles in the release of insulin and glucagon and in the protection of β cells from oxidative stress. We then discuss how current recommended methods of CFRD diagnosis are not appropriate, as continuous glucose monitoring (CGM) becomes more effective, practical and cost-effective. Finally, we evaluate emerging treatments which have narrowed the mortality gap within the CF patient group. In the future, pharmacological potentiators and correctors directly targeting CFTR show huge promise for both CFRD and the wider CF patient groups.